The Effect Of Trust And Risk On Interest Using Mobile Banking - Isa, Muhammad; Fadlilah, Hamni; Hamid, Azwar; Lestari, Emmi (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
PT. Bank Sumut Syariah Branch Padangsidimpuan provides mobile banking services, but this service is less attractive to customers. The purpose of the study was to determine the effect of trust and risk partially and simultaneously on the interest in using mobile banking on customers of PT. Bank Sumut Padangsidimpuan Sharia Branch. This research is quantitative research. The sample used in this study were 100 respondents. The sampling technique used was accidental sampling. Data analysis used is validity test, reliability test, normality test, classical assumption test, t test and F test using SPSS 24 tool. The results showed that there was an influence of trust on the interest in using mobile banking on customers of PT. Bank Sumut Syariah Branch Padangsidimpuan, there is a risk effect on interest in using mobile banking on customers of PT. Bank Sumut Syariah Branch Padangsidimpuan and there is the influence of trust and risk simultaneously (together) on the interest in using mobile banking on customers of PT. Bank Sumut Syariah Branch Padangsidimpuan .Keywords: Trust, Interest Using, Risk